Analysis of swimming performance using advanced technology - Havriluk, R.
Every coach and athlete looks for ways to improve. The search for a competitive advantage spans the range of technologies - from naked eye observation (basic) to synchronized video and force analysis (advanced) - that aim to help both coach and athlete. Gaining the most benefit from advanced technology involves employing a variety of analysis procedures. For example, technology that measures hand force clearly identifies stroke-to-stroke variations in how the hand presses on the water to generate force (Figure 1). When synchronized with video, force variations within each stroke indicate the exact arm position that limits performance. While these analysis procedures require time and effort, the potential for improvement is substantial - often more than .1 second per stroke - for even the fastest swimmers.